2016
DOI: 10.3168/jds.2015-9755
|View full text |Cite
|
Sign up to set email alerts
|

Dairy farmers’ use and non-use values in animal welfare: Determining the empirical content and structure with anchored best-worst scaling

Abstract: In this study, we sought to identify empirically the types of use and non-use values that motivate dairy farmers in their work relating to animal welfare of dairy cows. We also sought to identify how they prioritize between these use and non-use values. Use values are derived from productivity considerations; non-use values are derived from the wellbeing of the animals, independent of the present or future use the farmer may make of the animal. In particular, we examined the empirical content and structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 31 publications
0
49
0
Order By: Relevance
“…Farmers' approaches to FAW are not just a question of rational and economic choice, attitudes and ethical views should be taken into account to understand their decision-making process [76]. Swedish researchers applied a "use values" and "non-use values" framework to understand the role of farmers' personal evaluations on FAW achievement [11,38,39,75,80]. Non-use values referred to the economic value farmers derived from the welfare of the animals (i.e., economic value not derived from the direct use of the animal) [11,38].…”
Section: Non-use Valuementioning
confidence: 99%
See 2 more Smart Citations
“…Farmers' approaches to FAW are not just a question of rational and economic choice, attitudes and ethical views should be taken into account to understand their decision-making process [76]. Swedish researchers applied a "use values" and "non-use values" framework to understand the role of farmers' personal evaluations on FAW achievement [11,38,39,75,80]. Non-use values referred to the economic value farmers derived from the welfare of the animals (i.e., economic value not derived from the direct use of the animal) [11,38].…”
Section: Non-use Valuementioning
confidence: 99%
“…Swedish researchers applied a "use values" and "non-use values" framework to understand the role of farmers' personal evaluations on FAW achievement [11,38,39,75,80]. Non-use values referred to the economic value farmers derived from the welfare of the animals (i.e., economic value not derived from the direct use of the animal) [11,38]. They showed that non-use values in FAW were important motivational factors underlying dairy farmers' decision making.…”
Section: Non-use Valuementioning
confidence: 99%
See 1 more Smart Citation
“…McInerney, 2004) and their marginal willingness to pay for increasing the welfare of their animals depends on their income, then economic performance may have a causal effect on animal welfare. Indeed, Swedish dairy farmers stated that they find it important to make enough profit in order to improve the way their dairy cows are kept (Hansson and Lagerkvist, 2016). Figure 1 illustrates the relationship between animal welfare and economic performance.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…In addition, they find the elements ‘impression on others’ and ‘product quality’ to be representations of paternalistic‐altruism‐related non‐use values (terminology as in Lagerkvist et al ., ). Hansson and Lagerkvist () used a best–worst scaling approach with 123 Swedish dairy farmers in order to determine the economic value that dairy farmers associate with the animal welfare of dairy cows. The authors found that farmers are especially influenced by non‐use values related to the dairy cows being ‘well kept’ for example.…”
Section: Introductionmentioning
confidence: 99%